The Role of Empowering Leadership in Enhancing Employee Performance - Dandri Widyo; Muhammad Galih Indrajaya; Intan Ratnawati (Arthatama: Journal of Business Management and Accounting, 2023)
This study examines the impact of empowering leadership on employee performance, focusing on its role in enhancing motivation, engagement, and innovation across various industries. Empowering leadership, characterized by providing autonomy and fostering trust, has been identified as a key factor influencing employee outcomes such as in-role performance, work engagement, and psychological empowerment. Through a qualitative approach, the research conducts a comprehensive literature review to analyze existing studies on empowering leadership in various sectors. Data analysis is performed descriptively, synthesizing findings to identify key themes and relationships between empowering leadership and employee performance. The review highlights how empowering leadership facilitates innovation, supports adaptation to technological changes, and contributes to overall organizational sustainability. Additionally, the study emphasizes the importance of psychological empowerment and intrinsic motivation as mediators in the leadership-performance relationship. The findings suggest that organizations that implement empowering leadership practices can enhance employee performance, foster innovation, and improve adaptability, thereby contributing to long-term organizational success.